Reconstruction of Al-Qur'an Study Material in the Teaching Book of Al-Qur'an Hadis at the Madrasah Aliyah Level - Muhammad Aji Nugroho (Institut Agama Islam Negeri (IAIN) Samarinda, 2020)
This study aims to determine the limitations and direction of developing subject matter in textbooks used by educators in contextualizing teaching materials with the reality faced by students, as a solution to enrich the knowledge of the material that has been presented in textbooks. The principles that are used as the basis in developing the teaching material of the Koran are conformity, constancy, and adequacy. This study utilizes text sources to obtain descriptive exploratory research data. The primary source used is the al-Qur'an textbook of Hadith written by Lilis Fauziah and Andi Setiawan. Research results obtained; 1) The distribution of material in class X seems to have been coherent and gradual although there are still overlaps in the material as in KD 2 and KD 3, and in class XI and XII the material is delivered only by theme, so that it does not seem coherent and is only a theme selection; 2) The material taught is in accordance with the psychological of students and has been able to read the phenomena around it. But there is material that needs to be developed so that it makes more use of logic in thinking than just memorizing theory; 3) In terms of application of learning the cognitive level of learning has touched, but the affective and psychomotor sides have not; 4) discussion about differences of opinion among scholars is not discussed thoroughly, potentially confusing students. Error in preparing multiple choice questions and answers. Forms of development reconstruction offered by researchers include; 1) In terms of suitability (relevance) Subject with SK and KD; 2) in terms of consistency of learning material; 3) in terms of the adequacy of the material presented; 4) and in terms of the consequences of developing subject matter.